Edukasi Pemakaian Masker Sesuai Standar Operational Prosedur (SOP) Untuk Mengurangi Resiko ISPA Pada Masyarakat Di Kelurahan Taba Baru Kecamatan Lubuklinggau Utara I - Anggi Cristasari; Darmawansyah, Darmawansyah; Amanda, Dela Putri; Rini, Aprilia Sapta; CDS , Oktavia Eka (Utami Publisher, 2025)
Acute respiratory tract inflammation disease abbreviated as ISPA is an acute inflammatory disease that links the upper respiratory tract to the lower respiratory tract. In Taba Baru Village, Lubuklinggau City, the incidence of ISPA is quite high, there are 26 cases of ISPA, especially in the Taba Baru Village area which is affected by air pollution and dust. The 2025 Real Work Lecture Program (KKN-T) of Dehasen University Bengkulu focuses on promotive and preventive ISPA through an educational approach, namely with the ISPA counseling method, education on the use of masks by following standard operating procedures (SOP) when outdoors, especially for flu sufferers so as not to infect others, providing free masks to people who participate in counseling, counseling using leaflets. This activity is carried out through collaboration with village officials, cadres and the local community. The results of the activity show an increase in public awareness regarding the importance of maintaining environmental cleanliness, preparing vitamins at home if the body feels unwell, you can consume vitamins to prevent ISPA. This program has proven effective as a promotive and preventive strategy for the community and can be applied in everyday life. Cross-sector collaboration and ongoing education are essential to support efforts to reduce the incidence of ISPA, as well as contribute to preventing the spread of ISPA.